2008
DOI: 10.1002/cncr.23702
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for functional outcome and survival after reirradiation for in‐field recurrences of metastatic spinal cord compression

Abstract: Objective: We examined whether glucose transporter 1 (GLUT1) deficiency causes common idiopathic generalized epilepsies (IGEs). Methods: The IGEs are common, heritable epilepsies that usually follow complex inheritance; currently little is known about their genetic architecture. Previously considered rare, GLUT1 deficiency, due to mutations in SLC2A1, leads to failure of glucose transport across the blood–brain barrier and inadequate glucose for brain metabolism. GLUT1 deficiency was first associated with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 55 publications
(87 reference statements)
3
25
0
Order By: Relevance
“…Most studies revealed that ambulatory function at time of diagnosis is the most important predictor for the postoperative ambulatory outcome 2,14,16,17,20,24) . The most important prognostic indicator for the prediction of ambulatory outcome is patients' pretreatment ambulatory status.…”
Section: Functional Outcomementioning
confidence: 99%
“…Most studies revealed that ambulatory function at time of diagnosis is the most important predictor for the postoperative ambulatory outcome 2,14,16,17,20,24) . The most important prognostic indicator for the prediction of ambulatory outcome is patients' pretreatment ambulatory status.…”
Section: Functional Outcomementioning
confidence: 99%
“…Radiation is usually considered for patients without neurological symptoms and can be well tolerated if the correct indications are made. 8,31,38,44,47 On the other hand, Lee et al, 26 in a series of 11 patients undergoing radiotherapy and 1 patient without treatment, and Conill et al 4 reporting on 6 cases treated with radiotherapy combined with steroids, showed that after a short period of clinical improvement, a rather fast decline occurred in neurological functions, sometimes within only a few days. Thus, one could assume that unless radiation leads to an expected rapid shrinking of the tumor, surgery should be considered even when patients are oligosymptomatic.…”
mentioning
confidence: 99%
“…Factors such as the patient's performance status and visceral metastases can be useful when attempting to prognosticate functional outcome for patients. 23 Knowledge of the prognosis is crucial during the assessment process, as those not appropriate for a specialist SCI rehabilitation programme can be redirected to more appropriate settings. This needs to be tempered, however, with the limited alternative options besides palliative care.…”
Section: Discussionmentioning
confidence: 99%